PEMANFAATAN ICT UNTUK INOVASI PEMBELAJARAN SENI MUSIK - Novianti, Dwi; Agus Setiawan; Rama Wijaya Abdul Rozak (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The digital era presents new challenges and opportunities in music art education. Information and Communication Technology (ICT) has been utilized to create innovations in learning, making it more interactive and engaging. This research aims to explore the implementation of ICT in music art education to improve the quality and learning outcomes of students. Using the literature review method, this research analyzes various studies that utilize applications such as MuseScore, Sibelius, and Kahoot. The research results show that the use of ICT in music learning can enhance students' motivation, theoretical understanding, and technical skills. Applications like MuseScore support the understanding of musical notation, Sibelius facilitates interactive music theory learning, and Kahoot creates an enjoyable learning atmosphere through a game-based approach. However, challenges such as the lack of teacher training, limited infrastructure, and access to technology have become major obstacles. In conclusion, the utilization of ICT has a significantly positive impact on music art education. The optimal integration of technology requires adequate infrastructure support and training for teachers. Thus, ICT can continue to be a driving force for innovation in music art education that is relevant to the needs of the digital era.